Uniformly assembled polypyrrole-covered bacterial cellulose/g-C3N4 flexible nanofiber membrane for catalytic degradation of tetracycline hydrochloride. (June 2022) - Zhou, Tang; Zhao, Lei; Wu, Dingsheng; Feng, Quan; Zhao, Baobao
Abstract: As an emerging and promising technology, photocatalytic technology can effectively remove trace organic pollutants such as tetracycline hydrochloride (TC-H, an antibiotic) in water. However, the research on photocatalysis is mainly focused on the powder photocatalyst, which is difficult to separate from the water body after use. Generally, fixing the photocatalytic material on a specific carrier can effectively avoid the above problems. In this article, we uniformly assembled g-C3 N4 on bacterial cellulose (BC) with 3D nanofiber network and enhance its catalytic activity by polypyrrole (PPy). Different from the modification of the photocatalyst in most studies, we have effectively improved the catalytic activity through the design of the support material and reactor in this work. The PPy@(BC/g-C3 N4 ) flexible membrane prepared has high-efficiency catalytic performance (64.28%, 2 h, TC-H) under a low-power xenon lamp (λ > 420 nm) in the reactor designed, which is 5.27 times the catalytic efficiency of the original BC/g-C3 N4 (12.20%, 2 h, TC-H). After 10 times of repeated use, it can stably retain more than 80% of the initial catalytic activity. Specifically, we propose to introduce oxygen in the active substrate generation stage and construct a photoelectrocatalytic reaction cell. This study can be used as a general strategy to prepare flexible membrane materials with high-efficiency catalytic properties. Highlights: Fabrication of polypyrrole-covered bacterial cellulose/g-C3 N4 flexible nanofibrous membranes General strategy for the preparation of flexible BC-based nanofibrous membrane materials Innovative introduction of oxygen to build photoelectric catalytic reactor Effectively improve the catalytic efficiency of g-C3 N4 -based materials under visible light